Review-Design of Drainage System of Kedungmundu Road, Semarang City with the Implementation of the Sustainable Urban Drainage System (SUDS) - Anik Sarminingsih; Dwi Siwi Handayani; Alinda Astriani (Universitas Diponegoro, 2022)
The drainage system in the Kedungmundu Road area has several channels that can no longer accommodate the rainwater discharge, resulting in runoff of rainwater in the drainage channel, which causes flooding and puddles of rainwater in the Kedungmundu Road Area. Drainage in the Kedungmundu Road area has problems such as silting channels due to garbage, soil sedimentation, and insufficient channel dimensions. In the hydrological analysis, the rainfall intensity is 129,586 mm/hour. As the hydraulic analysis, the drainage channel is normalised by dredging sediment in the channel. If there is still rainwater runoff, additional channel dimensions are carried out, taking into account the existing conditions that only Karanggawang Lama road, H. Abdurochman road, and Kedungmundu Lama road changed. Channel dimensions, while for other channels, it is not possible to change the channel dimensions for that, it is necessary to apply SUDS. The Sustainable Urban Drainage System, or in SWMM 5.1 called Low Impact Development, is carried out using rainwater harvesting (Rain Barrel) and Permeable Pavement. The recapitulation of the application of the LID concept in the planning area is known to cover an area of 8.3 hectares of the total planning area of 54.48 hectares. This LID concept can reduce the total runoff value in each sub-catchment, thereby reducing the amount of rainwater discharge that enters the drainage channel with a percentage decrease in the average total runoff value of 19%. The Budget Plan needed to rehabilitate canals and dredging sediments and implement the Sustainable Urban Drainage System (SUDS) is around IDR 5,405,300,000.